Resin composition and molded article

JP7641133B2Active Publication Date: 2025-03-06GLOBAL POLYACETAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021025223
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-19
Publication Date
2025-03-06
Estimated Expiration
2041-02-19

AI Technical Summary

Benefits of technology

【0006】 本発明により、成形品としたときに、反りが生じにくく、かつ、成形収縮率に異方性が生じにくく、さらに、耐衝撃性に優れた樹脂組成物、および、成形品を提供可能になった。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641133000004
    Figure 0007641133000004
  • Figure 0007641133000001
    Figure 0007641133000001
  • Figure 0007641133000002
    Figure 0007641133000002
Patent Text Reader

Abstract

To provide a resin composition which prevents warpage when formed into a molding and prevents anisotropy in a molding shrinkage ratio, and is excellent in impact resistance, and a molding.SOLUTION: A resin composition contains 110-200 pts.mass of a reinforcement filler with respect to 100 pts.mass of a polyamide resin, where the polyamide resin contains a diamine-derived constitutional unit and a dicarboxylic acid-derived constitutional unit, 70 mol% or more of the diamine-derived constitutional unit is derived from at least one of meta-xylylene diamine and para-xylylenediamine, 70 mol% or more of the dicarboxylic acid-derived constitutional unit contains a polyamide resin derived from α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 20 carbon atoms, the reinforcement filler is a glass fiber having a flat cross section and a glass flake having a thickness of 0.1-2.0 μm, and a mass ratio of the glass fiber to the glass flake is 1.1 to 4.7.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a molded article, and more particularly to a resin composition and a molded article using a polyamide resin. [Background technology]

[0002] Polyamide resins have excellent mechanical and other physical and chemical properties, and are therefore widely used in vehicle parts, electrical and electronic equipment parts, other precision equipment parts, etc. In order to enhance the mechanical strength of molded products made from polyamide resins, reinforcing fillers such as glass fibers are sometimes blended into polyamide resins. Specifically, Patent Document 1 discloses a polyamide molding composition comprising (A) 28.0 to 64.9 mass% of at least one polyamide, (B) 15.0 to 40.0 mass% of glass fiber, (C) 15.0 to 35.0 mass% of glass flakes having a particle thickness in the range of 0.3 to 2.0 μm, (D) 0.1 to 2.0 mass% of a heat stabilizer, and (E) 0 to 5.0 mass% of an additive, with the condition that the total of components (B) and (C) is in the range of 35.0 to 65.0 mass% of the total of components (A) to (E), and the total of components (A) to (E) is 100 mass%. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-180280 A Summary of the Invention [Problem to be solved by the invention]

[0004] As mentioned above, reinforcing fillers are blended to increase mechanical strength, but depending on the type of reinforcing filler, the molded product may warp or have anisotropy in its molding shrinkage rate, especially when the molded product is a thin-walled product. In order to suppress warping and anisotropy, it is useful to blend glass flakes as a reinforcing filler, but blending glass flakes results in poor impact resistance. The present invention aims to solve these problems, and to provide a resin composition and a molded article which, when molded into a molded article, is less likely to warp, is less likely to have anisotropy in molding shrinkage rate, and has excellent impact resistance. [Means for solving the problem]

[0005] As a result of the investigation by the inventors of the present invention under the above-mentioned circumstances, it was found that the above-mentioned problems could be solved by using a specific polyamide resin as the polyamide resin and blending flat glass fiber and specific glass flakes in a specific ratio as the reinforcing filler. Specifically, the above-mentioned problems were solved by the following means. <1> A resin composition comprising 110 to 200 parts by mass of a reinforcing filler relative to 100 parts by mass of a polyamide resin, the polyamide resin comprising a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, 70 mol % or more of the diamine-derived structural units being derived from at least one of meta-xylylenediamine and para-xylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural units being derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms, the reinforcing filler being glass fiber having a flat cross section and glass flakes having a thickness of 0.1 to 2.0 μm, and a mass ratio of the glass fiber to the glass flakes, glass fiber / glass flakes, of 1.1 to 4.7. <2> The mass ratio of the glass fibers to the glass flakes, glass fibers / glass flakes, is 1.7 to 4.7; <1> The resin composition according to claim 1. <3> The α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms includes adipic acid and / or sebacic acid. <1> or <2> The resin composition according to claim 1. <4> When the resin composition is molded into a molded product having a size of 100 mm x 100 mm x 1 mm thickness, the amount of warping of the molded product is 0.40 mm or less. <1> ~ <3> The resin composition according to any one of the above items 1 to 5, wherein the amount of warpage refers to the difference in height between the highest point and the lowest point of the test piece when the molded article is placed on a reference stand. <5> The resin composition was molded into an ISO test piece having a thickness of 4 mm, and the notched Charpy impact strength according to ISO-179 was 12.0 kJ / m 2 That's all. <1> ~ <4> 10. The resin composition according to claim 9 . <6> The resin composition is used for a reel member of a fishing tackle. <1> ~ <5> 10. The resin composition according to claim 9 . <7> <1> ~ <6> 2. A molded article formed from the resin composition according to claim 1. Effect of the Invention

[0006] According to the present invention, it is possible to provide a resin composition and a molded article which, when molded into a molded article, is unlikely to warp, is unlikely to have anisotropy in molding shrinkage rate, and further has excellent impact resistance. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 is a schematic diagram for explaining a method for measuring the height of warpage in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified. In cases where the standards shown in this specification differ depending on the year and the measurement method, etc., they shall be based on the standards as of January 1, 2021, unless otherwise stated.

[0009] The resin composition of the present embodiment is characterized in that it contains 110 to 200 parts by mass of a reinforcing filler relative to 100 parts by mass of a polyamide resin, the polyamide resin contains diamine-derived structural units and dicarboxylic acid-derived structural units, 70 mol % or more of the diamine-derived structural units are derived from at least one of meta-xylylenediamine and para-xylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms, the reinforcing filler is glass fiber having a flat shape and glass flakes having a thickness of 0.1 to 2.0 μm, and the mass ratio of the glass fiber to the glass flakes, glass fiber / glass flakes, is 1.1 to 4.7. By adopting such a constitution, it is possible to obtain a resin composition which is unlikely to warp when molded into a molded article, is unlikely to cause anisotropy in the mold shrinkage rate, and has excellent impact resistance. Furthermore, it is possible to obtain a molded article which is excellent in mechanical strength other than impact resistance. That is, by including a polyamide resin containing a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, in which 70 mol % or more of the diamine-derived structural units are derived from at least one of metaxylylenediamine and paraxylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms (hereinafter sometimes referred to as a "xylylenediamine-based polyamide resin"), the anisotropy of the molded article can be effectively reduced, and the amount of warpage can also be reduced. Furthermore, the appearance of the obtained molded article can be improved. In addition, by appropriately adjusting the ratio of glass fiber to glass flake in the reinforcing filler, the anisotropy of the molded product is effectively reduced, the amount of warping is also reduced, and impact resistance is improved. Hereinafter, the resin composition of the present embodiment will be described in detail.

[0010] <Polyamide resin> The polyamide resin used in this embodiment contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and contains a polyamide resin (xylylenediamine-based polyamide resin) in which 70 mol % or more of the diamine-derived structural units are derived from at least one of metaxylylenediamine and paraxylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural units are derived from α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. By using a xylylenediamine-based polyamide resin, a molded product with small anisotropy and small warpage can be obtained. Furthermore, since the resin cures slowly, a molded product with excellent appearance can be obtained.

[0011] In the xylylenediamine-based polyamide resin used in this embodiment, preferably 80 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 99 mol % or more of the diamine-derived structural units are derived from xylylenediamine. The xylylenediamine-derived structural units are preferably metaxylylenediamine-derived structural units and / or paraxylylenediamine-derived structural units, and it is more preferable that 60 to 100 mol % of the xylylenediamine-derived structural units are metaxylylenediamine-derived structural units and 40 to 0 mol % are paraxylylenediamine-derived structural units (however, the total does not exceed 100 mol %, and it is preferable that the total is 90 to 100 mol %).

[0012] Diamines other than xylylenediamine that can be used as the raw diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine; 1,3-bis(aminomethyl)silane; Examples of such diamines include alicyclic diamines such as cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, paraphenylenediamine, and bis(aminomethyl)naphthalene. These can be used alone or in combination of two or more.

[0013] In the xylylenediamine-based polyamide resin used in the present embodiment, preferably 75 mol % or more, more preferably 85 mol % or more, even more preferably 95 mol % or more, and even more preferably 99 mol % or more of the dicarboxylic acid-derived structural units are derived from α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms (preferably adipic acid and / or sebacic acid).

[0014] The α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 20 carbon atoms is preferably an α,ω-straight-chain aliphatic dicarboxylic acid having 4 to 12 carbon atoms, and more preferably an α,ω-straight-chain aliphatic dicarboxylic acid having 6 to 12 carbon atoms. Examples of the α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, adipic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid, and adipic acid and / or sebacic acid are more preferred, and sebacic acid is even more preferred. The α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms can be used alone or in combination of two or more.

[0015] Examples of dicarboxylic acid components other than the above-mentioned α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms include phthalic acid compounds such as isophthalic acid, terephthalic acid, and orthophthalic acid, and isomers of naphthalenedicarboxylic acids such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. These can be used alone or in combination of two or more kinds.

[0016] In particular, the xylylenediamine-based polyamide resin is preferably a polyamide resin in which 70 mol % or more of the diamine-derived structural units are derived from xylylenediamine, 70 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms, and 60 mol % or more of the xylylenediamine-derived structural units are metaxylylenediamine-derived structural units.

[0017] A first preferred embodiment of the xylylenediamine-based polyamide resin is a polyamide resin in which 70 mol % or more of the diamine-derived constituent units are derived from xylylenediamine, 70 mol % or more (preferably 80 mol % or more, more preferably 90 mol % or more) of the dicarboxylic acid-derived constituent units are derived from adipic acid, and 60 mol % or more (preferably 80 mol % or more, more preferably 90 mol % or more) of the xylylenediamine-derived constituent units are constituent units derived from metaxylylenediamine.

[0018] A second preferred embodiment of the xylylenediamine-based polyamide resin is a polyamide resin in which 70 mol % or more (preferably 80 mol % or more, more preferably 90 mol % or more) of the diamine-derived structural units are derived from xylylenediamine, 70 mol % or more (preferably 80 mol % or more, more preferably 90 mol % or more) of the dicarboxylic acid-derived structural units are derived from sebacic acid, 60 to 90 mol % of the xylylenediamine-derived structural units are meta-xylylenediamine-derived structural units, and 40 to 10 mol % are para-xylylenediamine-derived structural units. The resin composition of the present embodiment preferably contains the xylylenediamine-based polyamide resin of the second embodiment.

[0019] In addition, the xylylenediamine-based polyamide resin is mainly composed of diamine-derived structural units and dicarboxylic acid-derived structural units, but does not completely exclude other structural units, and may contain lactams such as ε-caprolactam and laurolactam, and aliphatic aminocarboxylic acid-derived structural units such as aminocaproic acid and aminoundecanoic acid. Here, the main component means that the total number of diamine-derived structural units and dicarboxylic acid-derived structural units is the largest among all structural units among the structural units constituting the xylylenediamine-based polyamide resin. In this embodiment, the total of diamine-derived structural units and dicarboxylic acid-derived structural units in the xylylenediamine-based polyamide resin preferably accounts for 90 mol% or more of all structural units, and more preferably accounts for 95 mol% or more.

[0020] The resin composition of the present embodiment may or may not contain a polyamide resin other than the xylylenediamine-based polyamide resin. The other polyamide resin may be an aliphatic polyamide resin or a semi-aromatic polyamide resin, and is preferably an aliphatic polyamide resin. Examples of the aliphatic polyamide resin include polyamide 6, polyamide 66, polyamide 11, and polyamide 12, with polyamide 66 being preferred. Examples of the semi-aromatic polyamide resin include polyamide 6T, polyamide 9T, polyamide 10T, polyamide 6I, polyamide 9I, polyamide 6T / 6I, and polyamide 9T / 9I. The content of the polyamide resin other than the xylylenediamine-based polyamide resin in the resin composition of the present embodiment is preferably 10 parts by mass or less, and more preferably 8 parts by mass or less, when the total polyamide resin is 100 parts by mass. The lower limit of the content of the other polyamide resin may be 0 parts by mass.

[0021] The resin composition of the present embodiment preferably contains polyamide resin in a proportion of 25% by mass or more of the resin composition, more preferably 30% by mass or more, even more preferably 35% by mass or more, and may contain polyamide resin in a proportion of 40% by mass or more. The upper limit of the polyamide resin content is preferably 47% by mass or less, and more preferably 46% by mass or less. The polyamide resin may be one type only, or two or more types may be included. When two or more types are included, the total amount is preferably within the above range.

[0022] <Reinforcing filler> The resin composition of the present embodiment contains 110 to 200 parts by mass of a reinforcing filler relative to 100 parts by mass of a polyamide resin. By containing the reinforcing filler, the mechanical strength of the obtained molded article can be increased. The total amount of the reinforcing filler is preferably 120 parts by mass or more relative to 100 parts by mass of polyamide resin. By making it equal to or more than the lower limit, the mechanical strength of the molded article tends to be further improved. In addition, the total amount of the reinforcing filler is preferably 180 parts by mass or less relative to 100 parts by mass of polyamide resin, more preferably 170 parts by mass or less, even more preferably 160 parts by mass or less, even more preferably 150 parts by mass or less, and even more preferably 140 parts by mass or less. By making it equal to or less than the upper limit, a molded article with better surface appearance can be obtained. In addition, the total proportion of the reinforcing filler (glass fiber having a flat cross section and glass flakes having a thickness of 0.1 to 2.0 μm) in the resin composition of this embodiment is preferably 50 mass % or more of the resin composition. By making it equal to or more than the lower limit, the mechanical strength of the molded article tends to be further improved. The total proportion of the reinforcing filler in the resin composition of this embodiment is preferably 70 mass % or less, more preferably 65 mass % or less, and even more preferably 60 mass % or less. By making it equal to or less than the upper limit, higher mechanical properties can be obtained while maintaining a good surface appearance. The resin composition of the present embodiment may contain only one type of reinforcing filler (glass fiber and glass flake), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0023] In this embodiment, the reinforcing filler is glass fiber having a flat cross section and glass flakes having a thickness of 0.1 to 2.0 μm (hereinafter, simply referred to as "glass flakes"), and the mass ratio of the glass fiber to the glass flakes, glass fiber / glass flakes, is 1.1 to 4.7. By using the glass fiber and the glass flakes in combination, the warpage and anisotropy of the molded article can be reduced, and the impact resistance of the molded article can be increased. The mass ratio of the glass fiber to the glass flake, glass fiber / glass flake, is preferably 1.2 or more, more preferably 1.4 or more, even more preferably 1.7 or more, and depending on the application, more preferably 3.0 or more, and even more preferably 4.0 or more. By making it equal to or more than the lower limit, the impact resistance of the molded article tends to be further improved. In addition, the mass ratio of the glass fiber to the glass flake, glass fiber / glass flake, is preferably 4.5 or less, and depending on the application, more preferably 3.0 or less, and even more preferably 2.0 or less. By making it equal to or less than the upper limit, the warpage and anisotropy of the molded article can be further reduced.

[0024] <<Glass fiber>> The glass fiber used in this embodiment is a glass fiber having a flat cross section. By using such glass fiber, the impact resistance of the obtained molded article can be effectively improved. Furthermore, the anisotropy of the obtained molded article tends to be reduced. Furthermore, the warpage of the obtained molded article tends to be reduced.

[0025] The glass fiber in this embodiment is glass made into a fibrous form, and includes glass fibers used as a reinforcing material for plastics. More specifically, the glass fiber in this embodiment is preferably a chopped glass fiber obtained by bundling 1,000 to 10,000 glass fibers and cutting them to a predetermined length. The cross section of the glass fiber is flat. The flat shape may be any shape such as an ellipse, an oval, a rectangle, a rectangle with semicircles on both short sides, a cocoon, etc. The flatness (long axis of the glass fiber / short axis of the glass fiber) is more preferably 2.5 to 10, further preferably 3 to 10, and particularly preferably 3.1 to 6.

[0026] The glass fiber is a fiber obtained by melt spinning a glass such as E glass (electrical glass), C glass (chemical glass), A glass (alkaline glass), S glass (high strength glass), R glass, D glass, and alkali-resistant glass, which is generally supplied, but is not particularly limited as long as it can be made into glass fiber. In the present embodiment, it is preferable that the glass fiber contains E glass.

[0027] The glass fiber used in this embodiment is preferably surface-treated with a surface treatment agent such as a silane coupling agent, for example, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, etc. The amount of the surface treatment agent attached is preferably 0.01 to 1 mass% of the glass fiber. Furthermore, if necessary, it is also possible to use a glass fiber that has been surface-treated with a lubricant such as a fatty acid amide compound or silicone oil, an antistatic agent such as a quaternary ammonium salt, a resin having a film-forming ability such as an epoxy resin or urethane resin, or a mixture of a resin having a film-forming ability with a heat stabilizer, a flame retardant, etc.

[0028] <<Glass flakes>> The glass flakes used in this embodiment have a thickness of 0.1 to 2.0 μm. By using such glass flakes, the impact resistance of the resulting molded product can be effectively improved. The thickness of the glass flakes refers to the average thickness. The thickness of the glass flakes is preferably 0.3 μm or more, more preferably 0.4 μm or more, even more preferably 0.5 μm or more, and even more preferably 0.6 μm or more. The thickness of the glass flakes is preferably 1.8 μm or less, more preferably 1.6 μm or less, even more preferably 1.4 μm or less, even more preferably 1.2 μm or less, even more preferably 1.0 μm or less, and even more preferably 0.8 μm or less. Here, the average thickness is measured by the following method. That is, the thickness of each of 100 or more glass flakes is measured using a scanning electron microscope (SEM) and the measured values ​​are averaged. The sample stage of the scanning electron microscope is adjusted by a sample stage fine adjustment device so that the cross section (thickness plane) of the glass flake is perpendicular to the axis of the electron beam of the scanning electron microscope.

[0029] The glass composition of the glass flakes is not particularly limited, and various glass compositions such as A glass, C glass, D glass, S glass, R glass, and E glass are applicable.

[0030] <<Other reinforcing fillers>> The resin composition of the present embodiment may or may not contain reinforcing fillers other than the glass fibers having a flat cross section and the glass flakes having a thickness of 0.1 to 2.0 μm. The resin composition of the present embodiment is preferably substantially free of other reinforcing fillers. Substantially free means that the content of other reinforcing fillers is 10% by mass or less of the blended amount of the reinforcing filler, preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less. The other reinforcing fillers in this embodiment do not include those equivalent to a nucleating agent, which will be described later.

[0031] <Nucleating agent> The resin composition of the present embodiment may contain a nucleating agent to adjust the crystallization rate. The type of nucleating agent is not particularly limited, but talc, boron nitride, mica, kaolin, barium sulfate, silicon nitride, and molybdenum disulfide are preferable, talc and boron nitride are more preferable, and talc is even more preferable. When the resin composition of the present embodiment contains a nucleating agent, the content thereof is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the polyamide resin. The upper limit of the content is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, even more preferably 6 parts by mass or less, and even more preferably 4 parts by mass or less. The resin composition of the present embodiment may contain only one type of nucleating agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0032] <Release agent> The resin composition of the present embodiment may contain a release agent. Examples of the release agent include aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic carboxylic acid amides, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, polysiloxane-based silicone oils, and waxes. As the wax, polyolefin wax, ketone wax, amide wax, ester wax, and paraffin wax are preferable, and ketone wax is more preferable. For details about the release agent, please refer to the descriptions in paragraphs 0034 to 0039 of JP 2017-115093 A and paragraphs 0068 to 0091 of JP 2018-184575 A, the contents of which are incorporated herein by reference.

[0033] When the resin composition of the present embodiment contains a release agent, the content thereof is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the polyamide resin, and is preferably 5.0 parts by mass or less, more preferably 4.0 parts by mass or less, and even more preferably 3.0 parts by mass or less. The resin composition of the present embodiment may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0034] <Other ingredients> The resin composition of the present embodiment may contain other components within the scope of the present embodiment. Examples of such additives include light stabilizers, antioxidants, heat stabilizers, flame retardants, flame retardant assistants, ultraviolet absorbers, fluorescent brighteners, anti-dripping agents, antistatic agents, anti-fogging agents, anti-blocking agents, flow improvers, weather resistance improvers, light resistance improvers, plasticizers, dispersants, and antibacterial agents. These components may be used alone or in combination of two or more. The content of these components is preferably in the range of 5% by mass or less of the resin composition. In the resin composition of this embodiment, the contents of the polyamide resin, the reinforcing filler, and other additives blended as necessary are adjusted so that the total of each component is 100% by mass. In the resin composition of this embodiment, the total of the polyamide resin, the reinforcing filler, the nucleating agent, and the release agent preferably accounts for 90% by mass or more of the resin composition, more preferably 95% by mass or more, and even more preferably 98% by mass or more.

[0035] <Physical properties of resin composition> In this embodiment, it is preferable that the bending properties are excellent. Specifically, the resin composition of the present embodiment, when molded to a thickness of 4 mm, preferably has a flexural modulus of 10.0 GPa or more, more preferably 14.0 GPa or more, and even more preferably 18.0 GPa or more, according to ISO 178. There is no particular upper limit to the flexural modulus, but 40.0 GPa or less is practical, and even 35.0 GPa or less will fully satisfy the required performance. The resin composition of the present embodiment, when molded to a thickness of 4 mm, preferably has a bending strength of 330 MPa or more, more preferably 340 MPa or more, and even more preferably 350 MPa or more, according to ISO 178. There is no particular upper limit to the bending strength, but it is practical to set it to, for example, 500 MPa or less, or even 450 MPa or less.

[0036] The resin composition of the present embodiment preferably has excellent impact resistance. Specifically, the resin composition of the present embodiment is molded into an ISO test piece having a thickness of 4 mm, and the notched Charpy impact strength according to ISO-179 is 12.0 kJ / m 2 It is preferable that the concentration is 13.0 kJ / m or more. 2 The upper limit of the notched Charpy impact strength is not particularly limited, but is preferably 25.0 kJ / m 2 The following is practical: 22.0 kJ / m 2 Even if it is less than this, it will be sufficient to meet the required performance.

[0037] The resin composition of the present embodiment preferably has a small amount of warpage. Specifically, when the resin composition of the present embodiment is molded into a molded product of 100 mm x 100 mm x 1 mm thickness, the amount of warpage of the molded product is preferably 0.40 mm or less, more preferably 0.39 mm or less. There is no particular lower limit for the amount of warpage, but 0.10 mm or more is practical, and even if it is 0.25 mm or more, the required performance is sufficiently satisfied.

[0038] <Method of producing resin composition> The resin composition of the present embodiment can be produced by a known method for producing a thermoplastic resin composition. As an embodiment of the method for producing the resin composition of the present embodiment, it is preferable to mix and knead a polyamide resin with a reinforcing filler and other components that are mixed as necessary. An example of such a resin composition is a pellet. Specifically, the polyamide resin, the reinforcing filler, and other components to be added as necessary are mixed in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded in a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader. The reinforcing filler is preferably fed from the middle of the extruder to prevent it from being crushed during kneading. Two or more components selected from each component may be mixed and kneaded in advance.

[0039] <Molded products> The molded article of the present embodiment is formed from the resin composition of the present embodiment. The method for producing the molded article of the present embodiment is not particularly limited. For example, the molded product of this embodiment may be produced by melt-kneading the components and then directly molding the components using various molding methods, or by melt-kneading the components and pelletizing them, and then melting them again and molding them using various molding methods.

[0040] The method for molding the molded product is not particularly limited, and any conventionally known molding method can be used, such as injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding), rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, and pressure molding.

[0041] The shape of the molded product of the present embodiment is not particularly limited and can be appropriately selected depending on the application and purpose of the molded product. Examples of the shape include plate-like, plate-like, rod-like, sheet-like, film-like, cylindrical, annular, circular, elliptical, gear-like, polygonal, irregularly shaped, hollow, frame-like, box-like, and panel-like shapes.

[0042] The application field of the molded product of this embodiment is not particularly limited, and it is widely used in automobile and other transportation machinery parts, general machine parts, precision machine parts, electronic and electrical equipment parts, office automation equipment parts, building materials and housing related parts, medical devices, leisure sports goods, play equipment, medical products, daily necessities such as food packaging films, defense and aerospace products, etc. In particular, the molded product of this embodiment has high impact resistance and achieves low warpage, and is therefore preferably used for curved members (e.g., housings) that require high impact resistance. Curved members include those in which at least a portion of the member is curved, those in which at least a portion of the member is bowl-shaped, and the like. An example of a curved housing is a reel member for fishing tackle. EXAMPLES

[0043] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. If the measuring instruments used in the examples are difficult to obtain due to discontinuation or the like, measurements can be made using other instruments with equivalent performance.

[0044] <Polyamide resin> MP10: M / P ratio = 7:3, synthesized according to the following synthesis example. MXD6: Polymetaxylylene adipamide, manufactured by Mitsubishi Gas Chemical Company, MX Nylon #6000 PA66: Manufactured by Toray Industries, Inc., CM3001-N

[0045] <Synthesis example of MP10 (M / P ratio = 7:3)> Sebacic acid was heated and dissolved in a reaction vessel under a nitrogen atmosphere. Then, while stirring the contents, a mixed diamine with a molar ratio of 3:7 of para-xylylenediamine (manufactured by Mitsubishi Gas Chemical Company) and meta-xylylenediamine (manufactured by Mitsubishi Gas Chemical Company) was gradually dropped under pressure (0.35 MPa) so that the molar ratio of diamine to sebacic acid became approximately 1:1, and the temperature was raised to 235°C. After the dropping was completed, the reaction was continued for 60 minutes to adjust the amount of components with a molecular weight of 1,000 or less. After the reaction was completed, the contents were taken out in a strand shape and pelletized with a pelletizer to obtain a polyamide resin (MP10, M / P = 7:3).

[0046] <Glass fiber> Flat GF: Glass fiber with a flat cross-section, E-glass, manufactured by Nitto Boseki Co., Ltd., CSG 3PA-810S, flatness ratio 4 Circular GF: Glass fiber with a circular cross-section, number average fiber diameter 10.5 ± 1.0 μm, E-glass, manufactured by Nippon Electric Glass Co., Ltd., T-756H, flatness ratio 1

[0047] <Glass flake> Thickness 0.7 μm: Glass flake, manufactured by Nippon Sheet Glass Co., Ltd., MEG160FY-M06 Thickness 5 μm: Glass flake, manufactured by Nippon Sheet Glass Co., Ltd., FLEKA REFG313

[0048] <Nucleating agent> Talc: Manufactured by Hayashi Kasei Co., Ltd., Micron White 5000S

[0049] <Release agent> CS8CP: Calcium montanate, manufactured by Nitto Kasei Kogyo Co., Ltd.

[0050] Examples 1 to 3, Comparative Examples 1 to 10 <Compound> Resin compositions (pellets) shown in Tables 1 to 3 below were produced. Specifically, the components other than glass fiber and glass flake were weighed out in the ratios (units: parts by mass) shown in Tables 1 to 3 below, and dry-blended, and then fed from the screw root of a twin-screw extruder (Shibaura Machine Co., Ltd., TEM26SS) using a twin-screw cassette weighing feeder (Kubota Corporation, CE-W-1-MP). Glass fiber and glass flake were fed from the side of the extruder using a vibration cassette weighing feeder (Kubota Corporation, CE-V-1B-MP), and melt-kneaded with resin components, etc. to obtain a resin composition. The temperature of the twin-screw extruder was set to 280°C.

[0051] <Flexural strength and flexural modulus> The pellets obtained above were dried at 120°C for 4 hours, and then injection molded into ISO tensile test specimens (4 mm thick) using an injection molding machine (manufactured by Nissei Plastic Industrial Co., Ltd., "NEX140III") under conditions of a cylinder temperature of 280°C and a mold temperature of 130°C. The flexural strength (unit: MPa) and flexural modulus (unit: GPa) were measured using the above ISO tensile test pieces (4 mm thick) in accordance with ISO 178. The results are shown in Tables 1 to 3.

[0052] <Charpy impact strength> The above ISO tensile test pieces (4 mm thick) were processed into notched test pieces according to JIS K7144. The notched test pieces were subjected to the notched Charpy impact strength (unit: kJ / m 2 The results are shown in Tables 1 to 3.

[0053] <Mold shrinkage anisotropy (TD / MD)> The pellets obtained above were dried at 120°C for 4 hours, and then injection molded into test pieces measuring 100 mm x 100 mm x 2 mm using a Nissei Plastic Industrial Co., Ltd. NEX80III under conditions of a cylinder temperature of 280°C and a mold temperature of 130°C. The dimensions of the obtained test piece in the resin flow direction (MD) and the direction perpendicular to the flow (TD) were measured, the molding shrinkage was calculated from the dimensions of the mold, and the anisotropy of the molding shrinkage was evaluated from the value obtained by dividing the molding shrinkage in TD by the molding shrinkage in MD. The results are shown in Tables 1 to 3. The closer the value calculated by this method is to 1, the smaller the anisotropy of the molding shrinkage and the better the dimensional accuracy and low warpage.

[0054] <Warpage amount> The resin composition (pellets) obtained above was dried at 120° C. for 4 hours, and then a test piece (100 mm×100 mm×1 mm) for measuring the amount of warpage was produced using an injection molding machine (NEX80III, manufactured by Nissei Plastic Industrial Co., Ltd.). During molding, the cylinder temperature was 280°C, and the mold temperature was 130°C (MXD6), 110°C (MP10), or 80°C (PA66) depending on the type of polyamide resin, which was the main component of the resin component. The test piece for measuring the amount of warpage obtained above (100mm x 100mm x 1mm) was placed on a reference stand, and the height of the highest part (Max height, unit: mm) and the height of the lowest part of the test piece (Min height, unit: mm) were measured using a three-dimensional shape measuring device, and the difference between them was calculated. Specifically, as shown in Figure 1, the height of the reference stand 1 was set to 0 mm, and the test piece 2 was placed on it, and the difference in height between the highest part 3 and the lowest part (usually the end of the test piece) was measured as the warpage 4. The three-dimensional shape measuring machine used was a VR-3000 / 3200 manufactured by Keyence Corp. The results are shown in Tables 1 to 3.

[0055] <Appearance> The pellets obtained above were dried at 120°C for 4 hours, and then injection molded into flat plates of 60mm x 60mm x 2mm using an injection molding machine (Nissei Plastic Industrial Co., Ltd., "NEX140III") at a cylinder temperature of 280°C and a mold temperature of 130°C. Five experts evaluated the pellets and made a majority decision. The evaluation was as follows: A: There is no reinforcing fiber floating on the surface of the molded product, and the surface is glossy. B: Other than the above, for example, reinforcing fibers are floating on the surface of the molded product.

[0056] [Table 1]

[0057] [Table 2]

[0058] [Table 3]

[0059] In the above Tables 1 to 3, the ratio of glass fiber to flake filler is a mass ratio. As is clear from the above results, the resin composition of the present invention was less likely to cause warping in the molded product, was less likely to cause anisotropy in the molding shrinkage rate of the molded product, and had high Charpy impact strength and other mechanical properties. Furthermore, the appearance was also excellent. In contrast, when the polyamide resin did not contain a xylylenediamine-based polyamide resin (Comparative Example 1), the anisotropy was large, and the amount of warpage was also large.Furthermore, the appearance of the molded product was poor. Furthermore, when the blending amount of glass fiber in the reinforcing filler was small (Comparative Examples 2 to 4 and 6), the Charpy impact strength was low. Moreover, when the glass fiber had a circular cross section (Comparative Examples 5 and 6), the anisotropy was large, and the Charpy impact strength was low. On the other hand, when the thickness of the glass flakes was large (Comparative Examples 7 and 8), the Charpy impact strength was low. Furthermore, when no glass flakes were blended (Comparative Example 9), the amount of warping was large. Moreover, when the amount of the reinforcing material blended was itself small (Comparative Example 10), the mechanical strength was insufficient. [Explanation of symbols]

[0060] 1 Reference stand 2. Test specimens 3. The tallest part 4. Warping

Claims

1. The composition contains 110 to 200 parts by mass of a reinforcing filler relative to 100 parts by mass of a polyamide resin, the polyamide resin comprises a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, 70 mol % or more of the diamine-derived structural units being derived from at least one of metaxylylenediamine and paraxylylenediamine, and 70 mol % or more of the dicarboxylic acid-derived structural units being derived from a xylylenediamine-based polyamide resin derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms; the reinforcing filler is glass fiber having a flat cross section and glass flakes having a thickness of 0.1 to 2.0 μm; A resin composition, wherein the mass ratio of the glass fibers to the glass flakes, glass fibers / glass flakes, is 1.4 to 4.7, The content of the polyamide resin other than the xylylenediamine-based polyamide resin in the resin composition is 10 parts by mass or less when the total polyamide resin is 100 parts by mass. Resin composition.

2. The resin composition according to claim 1, wherein the mass ratio of the glass fibers to the glass flakes, glass fibers / glass flakes, is 1.7 to 4.

7.

3. 3. The resin composition according to claim 1, wherein the α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms includes adipic acid and / or sebacic acid.

4. The resin composition according to any one of claims 1 to 3, wherein when the resin composition is molded into a molded article of 100 mm x 100 mm x 1 mm thick, the amount of warping of the molded article is 0.40 mm or less; the amount of warping refers to the difference in height between the highest point and the lowest point of the test piece when the molded article is placed on a reference stand.

5. The resin composition was molded into an ISO test piece having a thickness of 4 mm, and the notched Charpy impact strength according to ISO-179 was 12.0 kJ / m 2 The resin composition according to any one of claims 1 to 4.

6. The resin composition according to any one of claims 1 to 5, which is used for a reel member of a fishing tackle.

7. A molded article formed from the resin composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Fiber-reinforced thermoplastic resin composition

    JP1990173047A

  • Thermoplastic resin composition

    JP1996225741A

  • Molded article from fiber-reinforced thermoplastic resin

    JP2008095066A

  • Resin composition and molded article

    JP2020033412A

  • Reinforced thermoplastic molding composition

    JP2020180280A